Internally displaced in Tigray (Northern Ethiopia): Management and sustainability of shelter and settlement - Samuel Bekele; Domenico Patassini; Jacopo Galli (Progress in Disaster Science)
Following the two-year war (2020−2022) in Tigray, Northern Ethiopia, more than two million people were internally displaced. A large number of internally displaced persons (IDPs) suffered precarious shelter and settlement conditions, resulting in unsafe, undignified, and substandard living environments. Construction of emergency shelter within a short timeframe, limited availability of humanitarian partners, logistical constraints, and scarce resources were among the major challenges. These issues were further exacerbated by the lack of a comprehensive assessment of shelter typologies, as well as traditional construction methods and settlement patterns. The aim of this study is to assess shelter typologies and construction systems, as well as to examine settlement characteristics, delivery, and management approaches. Particular emphasis is placed on innovative shelter solutions and sustainability. A multi-site case study, combined with within- and cross-case analysis, enabled the collection of both qualitative and quantitative data across multiple locations. Data were gathered through interviews, questionnaires, focus group discussions, on-site observations, and visual documentation, supported by a comprehensive literature review. The study identified sixteen distinct shelter typologies, each varying in design, construction methods, building materials, and longevity across four primary settlement morphologies.Settlements were created through IDPs self construction or direct by humanitarian partners.